Unveiling gender dynamics and disparities in the aquaculture value chain: evidence from Ogun and Delta States, Nigeria - Adam, Rahma; Njogu, Lucy; Ouko, Kevin; Rajaratnam, Surendran; Adeleke, Lydia; Ogunya, Lydia; Akuwa, Elizabeth; Farnworth, Cathy; Fregene, Bernadette (Springer (part of Springer Nature), 2025)
This paper offers new insights into gender norms, roles, participation, relations, and benefits derived by women and men engaged in the aquaculture sector in Ogun and Delta States in Nigeria. Data were collected using mixed methods, including structured surveys of 410 farmers, 175 market actors, and 53 input suppliers, 116 semi-structured key informant interviews, and 11 focus group discussions (FGDs). Overall results of the study revealed the linkages within the aquaculture value chain, which was highly gendered, with men dominating all the three main stages of the value chain as indicated by Duncan's index of dissimilarity of 17.35%. Results also revealed a gender difference in the value of assets, ownership, and wage rate among men and women participants in paid labor in the input supply and fish trading segments. Men tended to realize more profits than women, indicating an imbalance in the distribution of benefits by gender along the aquaculture value chain. Results revealed that the participation of women in decision-making was relatively high, attributable to their involvement in aquaculture value chain activities. The findings highlight the need for governments, development agencies, and non-governmental organizations to address gender disparities in policies designed to improve the imbalance in the distribution of benefits between women and men.